Feasibility of using an automated call service to collect quality of life and functional outcome data in trauma patients - Jan O Jansen; Russell L Griffin; Shannon W Stephens; Emily W Baird; Jonathan A Black; John P Winkler (Trauma Surgery & Acute Care Open)
Objectives Following up trauma patients after discharge, to evaluate their subsequent quality of life and functional outcomes, is notoriously difficult, time consuming, and expensive. Automated systems are a conceptually attractive solution. We prospectively assessed the feasibility of using a series of automated phone calls administered by Emmi Patient Engagement to survey trauma patients after discharge.Methods Recruitment into the study was incorporated into the patient discharge process by nursing staff. For this pilot, we included trauma patients discharging home and who were able to answer phone calls. A script was created to evaluate the Extended Glasgow Outcome Scale and the EuroQol EQ-5D to assess functional status and quality of life, respectively. Call attempts were made at 6 weeks, 3 months, 6 months, and 1 year after discharge.Results A total of 110 patients initially agreed to participate. 368 attempted patient encounters (calls or attempted calls) took place, with 104 (28.3%) patients answering a least one question in the study. 21 unique patients (19.1% of those enrolled) completed 27 surveys.Conclusions Automated, scripted phone calls to survey patients after discharge are not a feasible way of collecting functional and quality of life data.Level of evidence Level II/prospective.